Sustainable energy production: Performance evaluation of a generator-set using cow dung-based biogas - Kusnadi, Kusnadi; Wahid, Mazlan Abdul; Yasin, Mohd Fairus Mohd; Rajani, Ahmad; Fudholi, Ahmad (National Research and Innovation Agency, 2024)
Interest in utilizing new and renewable energy sources, commonly known as bioenergy, has significantly grown in the past decade due to the mounting environmental concerns, such as air pollution, global warming, and ozone layer depletion, resulting from the accelerated consumption of fossil fuels. Biogas, derived from the anaerobic decomposition of organic materials like cow dung, presents a viable solution due to its high methane content and calorific value. This study aims to assess the performance of biogas-fueled generator sets utilizing cow dung as the raw material for biogas production. The generator set employed has a power capacity of 2,500 Watts, and various load variations ranging from 150 to 350 Watts were applied. The parameters measured include voltage, current, biogas discharge, and efficiency. The findings indicate that the generator's output power for the five load variations of 150, 200, 250, 300, and 350 Watts are 150, 226.7, 266, 298.3, and 372.3 Watts, respectively. Moreover, the fuel consumption rates range from 0.013 to 0.009 kg/minute for the 150 to 350 Watts load, respectively. Notably, the 350 Watts loading exhibits the highest efficiency compared to other load variations, with an efficiency percentage of 14.51 %. This research advances our knowledge of the useful uses of biogas in generating systems, where its use is growing.